Highly diverse chromoviruses of Beta vulgaris are classified by chromodomains and chromosomal integration - Weber, Beatrice (BioMed Central, 2013)
BACKGROUND: Chromoviruses are one of the three genera of Ty3-gypsy long terminal repeat (LTR) retrotransposons, and are present in high copy numbers in plant genomes. They are widely distributed within the plant kingdom, with representatives even in lower plants such as green and red algae. Their hallmark is the presence of a chromodomain at the C-terminus of the integrase. The chromodomain exhibits structural characteristics similar to proteins of the heterochromatin protein 1 (HP1) family, which mediate the binding of each chromovirus type to specific histone variants. A specific integration via the chromodomain has been shown for only a few chromoviruses. However, a detailed study of different chromoviral clades populating a single plant genome has not yet been carried out. RESULTS: We conducted a comprehensive survey of chromoviruses within the Beta vulgaris (sugar beet) genome, and found a highly diverse chromovirus population, with significant differences in element size, primarily caused by their flanking LTRs. In total, we identified and annotated full-length members of 16 families belonging to the four plant chromoviral clades: CRM, Tekay, Reina, and Galadriel. The families within each clade are structurally highly conserved; in particular, the position of the chromodomain coding region relative to the polypurine tract is clade-specific. Two distinct groups of chromodomains were identified. The group II chromodomain was present in three chromoviral clades, whereas families of the CRM clade contained a more divergent motif. Physical mapping using representatives of all four clades identified a clade-specific integration pattern. For some chromoviral families, we detected the presence of expressed sequence tags, indicating transcriptional activity. CONCLUSIONS: We present a detailed study of chromoviruses, belonging to the four major clades, which populate a single plant genome. Our results illustrate the diversity and family structure of B. vulgaris chromoviruses, and emphasize the role of chromodomains in the targeted integration of these viruses. We suggest that the diverse sets of plant chromoviruses with their different localization patterns might help to facilitate plant-genome organization in a structural and functional manner.